2023
DOI: 10.1126/science.add2814
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory limits success of vegetation restoration globally

Changlin Xu,
Brian R. Silliman,
Jianshe Chen
et al.

Abstract: Restoring vegetation in degraded ecosystems is an increasingly common practice for promoting biodiversity and ecological function, but successful implementation is hampered by an incomplete understanding of the processes that limit restoration success. By synthesizing terrestrial and aquatic studies globally (2594 experimental tests from 610 articles), we reveal substantial herbivore control of vegetation under restoration. Herbivores at restoration sites reduced vegetation abundance more strongly (by 89%, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 666 publications
0
7
0
Order By: Relevance
“…seeds, corms and seedlings) to expedite the recovery of foundation species (Derksen-Hooijberg et al, 2018;Silliman et al, 2015). Active restoration has also been widely reported to suffer from intense grazing pressure in many ecosystems (Bakker et al, 2018;MacDougall et al, 2010;Xu et al, 2023). This was also the case at our restoration site in the Yangtze River estuary (Qian et al, 2021).…”
Section: Towards Co-restoration Of Keystone Predators and Foundation ...mentioning
confidence: 57%
See 1 more Smart Citation
“…seeds, corms and seedlings) to expedite the recovery of foundation species (Derksen-Hooijberg et al, 2018;Silliman et al, 2015). Active restoration has also been widely reported to suffer from intense grazing pressure in many ecosystems (Bakker et al, 2018;MacDougall et al, 2010;Xu et al, 2023). This was also the case at our restoration site in the Yangtze River estuary (Qian et al, 2021).…”
Section: Towards Co-restoration Of Keystone Predators and Foundation ...mentioning
confidence: 57%
“…Loss of keystone predators has been widely reported to release grazers out of predator control, intensify grazing pressure and drive collapse of ecosystems characterized by foundation species, such as salt marshes, grasslands and forests (Altieri et al, 2012;Atkins et al, 2019;Estes et al, 2011). Although an increasing number of studies have shown that controlling grazers can greatly enhance restoration of foundation species (Derksen-Hooijberg et al, 2018;Qian et al, 2021;Xu et al, 2023) and trophic rewilding-a strategy that adopts species introductions to restore top-down trophic interactions and balances of different trophic levels to promote selfregulating biodiverse ecosystems-is increasingly called for as a tool to enhance the passive recovery of natural ecosystems (Svenning et al, 2016), approaches to restore foundation species continue to largely neglect keystone predators.…”
Section: Introductionmentioning
confidence: 99%
“…While not explored in depth in this review, the implications of better understanding plant trait relationships with large herbivores will also aid in the design and implementation of plant-focused restoration projects as it has for other disturbances and ecosystem services (Laughlin, 2023a). Insights from applying a traits perspective to rewilding studies could also inform projects focused seeding and planting where herbivore pressure is a key bottleneck to survival and growth (Xu et al, 2023). Tools for designing species mixes for restoration based on their traits exist and are beginning to be used in an experimental setting (Andres et al, 2023;Ladouceur et al, 2022;Laughlin et al, 2018).…”
Section: Anthrop Og Enic Comple Xitie S In Pl Ant Tr Ait Re S P On S ...mentioning
confidence: 99%
“…by weeds (Yannelli et al, 2018). However, herbivores can considerably reduce the establishment of plants in restoration projects (Xu et al, 2023). Therefore, while we focus here on how traits will help us predict and understand the ecosystem effects of large mammal reintroductions for rewilding, insights may also inform the design of species mixtures for seeding and planting activities where herbivory provides a strong bottleneck on establishment.…”
Section: Anthrop Og Enic Comple Xitie S In Pl Ant Tr Ait Re S P On S ...mentioning
confidence: 99%
“…Since the 1990s, meta-analysis has been introduced into ecological research and has received considerable attention and significant development [22][23][24][25]. Meta-analysis is widely employed in the field of ecology today [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%